Estimating economic and epidemiological burden of hepatitis C in Egypt, 2015-2025 - Mankoula, Wessam (AUC Knowledge Fountain, 2015)
Hepatitis C is the most pressing public health challenge in Egypt where Hepatitis C Virus (HCV) prevalence is the highest in the world. In 2015, Egypt Health Issues Survey showed that 10% of Egyptians between 15 – 59 years of age had been infected with HCV infection, while 7% are chronic active hepatitis C patients. This paper aims to estimate the current and future economic and epidemiological burden of HCV between 2015 and 2025. In addition, it compares the impact of different scenarios for management of this huge public health problem to identify the most cost effective strategy capable of reducing the economic and epidemiological burden of this disease at the country level. A Markov model representing hepatitis C progression was established showing the prognosis among HCV infected cohort within different age groups where the members of each group go through predefined states of health over one-year time cycles till 2025. The burden of hepatitis C will be estimated through calculating different transition probabilities and calculating the direct and indirect healthcare cost of the proportion of members who go through each stage of the disease and its complications. Under the current management strategy of 125,000 patients/year, it is estimated that chronic active HCV patients will show minimal decrease to reach about 4.1 million cases, with high economic burden of this strategy is very high where the direct costs are estimated $23.3 billion, and the total costs are $48.3 billion between 2015-2025. While increasing the treatment rate to reach one million patient annually for 5 years in addition to decreasing the annual incidence in the coming 10 years will drop HCV cases to about 636 thousands by 2025, and with only $16.2 billion as a direct costs, and total costs $34.2 billion between 2015-2025 which is 29.2% lower than the current management scenario.